Impact of intravertebral cleft types on percutaneous kyphoplasty outcomes in osteoporotic vertebral compression fractures - Yuzhi Ning; Yuxuan Sun; Shuang Xu; Heng Wu; Daxiong Feng; Qing Wang; Song Wang (Scientific Reports)
Abstract This study aimed to investigate the therapeutic effects and radiographic results of percutaneous kyphoplasty (PKP) in patients with osteoporotic vertebral compression fractures (OVCFs) with or without intravertebral clefts (IVCs). Clinical data from 288 patients with OVCFs who underwent PKP surgery were retrospectively analyzed and stratified into the liquid-IVC group, gas-IVC group, and non-IVC group through magnetic resonance imaging. The baseline characteristics revealed that the liquid-IVC group included older patients and a greater proportion of male participants (P < 0.05). All patients reported pain relief, vertebral height (VH) improvement, and kyphotic angle correction immediately after PKP surgery (P < 0.05). The bone cement distribution score was significantly lower (P < 0.05) in the liquid-IVC group than in the other two groups, but the VH improvement rate (VHIR), VH change rate (VHCR) and recollapse rate were significantly greater (P < 0.05). Moreover, the non-IVC group demonstrated a significantly lower incidence of postoperative bone cement leakage than the other two groups did (P < 0.05). However, the VH and Cobb angle significantly decreased in all groups during the follow-up period (P < 0.05). Further analysis revealed a significant correlation between bone cement distribution and IVC (by evaluating the injury zone score) in the liquid-IVC group (R2 = 0.371, P < 0.05), whereas no significant difference was found in the other two groups (R2 = −0.123, P = 0.218). In conclusion, PKP surgery is effective in treating OVCFs with or without IVCs, but liquid-filled IVCs exhibit a worse therapeutic effect on radiographic parameters than gas-filled IVCs and non-IVCs during follow-up. Patients with liquid-filled IVCs also have limited and IVC-related bone cement distribution.